Public Animo in the 2020 Gubernatorial Election in Central Kalimantan during the Covid-19 Pandemic Era: Religious and Cultural Approaches - Erawati, Desi; Harmain, Harmain (Millah: Journal of Religious Studies, 2024)
Many observers believe that holding general elections during a pandemic is ineffective in attracting public interest, including in Central Kalimantan. This study aimed to examine how the public's animo in the gubernatorial election during the Covid-19 pandemic, through religious and cultural approaches, in which the Central Kalimantan people still respected traditional and religious leaders as role models. This research used descriptive qualitative data collected through interviews with traditional and religious leaders and related documents obtained from election administrators. The findings showed that socialization was a reasonably good tool and strategy carried out by traditional leaders and religious leaders at specific events with cultural (local tradition, Dayak language) and religious approaches (through speech in churches and other religious places of worship). Socialization by traditional and religious leaders contributes to public animo in the gubernatorial election in Central Kalimantan.